(untitled) (Research, Society and Development, 2020)
Prenatal care is essential for maintaining the health of the pregnant woman and the fetus, being assisted by a multiprofessional apparatus. Nurses stand out in health promotion and education throughout prenatal consultations, supporting pregnant women about gestational care and risks. This study aimed to investigate through an integrative literature review the role of nurses in education and health promotion in prenatal care. The research was carried out in a descriptive manner, through an integrative literature review in the databases of the virtual health library (vhl) and scielo (electronic library online), between the years 2010-2020. The results showed an improvement in the performance of nurses in prenatal care, with the establishment of bonds with pregnant women and the development of actions that promote the education of pregnant women, especially in the face of aspects such as breastfeeding, food and physical activity. However, we conclude that such actions are still limited and need scientific improvement, in order for nurses to act fully in favor of the effectiveness and qualification of prenatal care.